Propuesta de una metodología de auditoría ambiental para el proceso productivo de las industrias lácteas del Cantón Mejía - Cóndor Galarza, Alexandra Denisse (2015)
This project presents a guide to the implementation of environmental audit in dairies of Canton Mejia, considering this economic sector as one of the most important activities in the economy of our country. For purposes of this methodology, concepts of auditing, quality, environmental regulation and control bodies are discussed further audit procedures applicable to design a model according to the sector, to identify the environmental impacts generated by the industry. Additionally, information and statistical data of the dairy industry in Ecuador, as well as major companies in the sector is included. Initially a situation analysis of the company and the observation of the activities are developed to determine the generated negative effects. Audit procedures are applied according to the reality of the industry and initially detected deviations, their level of compliance is assessed with respect to the applicable environmental regulations, determining the level of pollution generated by productive activities affecting environmental fields: air, water, land, natural resources and people. This becomes essential to reduce, mitigate or remedy the negative impacts caused during production, by proposing recommendations to the audited entity, through the submission of a final report, also all work performed is reflected and the detected deviations. Finally, the proposed recommendations are evaluated through the application of indicators, which measure the level of compliance within previously established deadlines.